Barriers and facilitators to end-of-life care in the adult intensive care unit: A scoping review - Emmanuel Kwame Korsah; Shelley Schmollgruber (Elsevier, 2023)
Aim: To identify qualitative studies that describe the barriers and facilitators nurses perceive and experience when delivering end-of-life care in the Adult Intensive Care Unit. Design: The design was a scoping review that followed the Joanna Briggs Institute methodology. Methods: There were four selected databases searched electronically to identify published qualitative studies. Data extraction was with a standard data extraction tool and independently extracted by two reviewers. Results: In total, 20 qualitative studies were eligible for result extraction. The majority of studies (19; 95%) presented findings on the barriers to end-of-life care, and a few (11; 55%) focused on the facilitators of end-of-life care. The provision of adequate end-of-life care training and education for nurses, formulation of policies and guidelines in the ICU, and working with family members are vital measures to enhancing the quality of care patients and families receive at the end of life. No Patient or Public Contribution: In this study no patient and members of the public were involved. Only published existing literature was used, hence, no patient or public contribution was needed.